2017
DOI: 10.3389/fpsyt.2017.00057
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Intersections of Trauma, Structural Adversity, and Psychosis among a Primarily African-American Sample: A Mixed-Methods Analysis

Abstract: Traumatic life events (TLEs) have been associated with multiple psychiatric diagnoses, including anxiety disorders, major depression, PTSD, and psychosis. To advance our understanding of the complex interactions between forms of adversity as they manifest across the lifespan, psychosis, and symptom content, we undertook a mixed-methods investigation of TLEs and psychosis. Our research explored the association between cumulative exposures, type of TLE, and proximity to the traumatic event and psychosis; the ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 76 publications
3
19
0
6
Order By: Relevance
“…Traumatic events are the prototype of eminently interpersonal, environmental factors that could significantly destabilize and alter subjective experience at various levels. 106 A history of neglect significantly increases the likelihood of developing schizophrenia (and other forms of clinical symptomology) 107,108 ; traumatic and other adverse events are also associated with the development of hallucinations in both clinical and nonclinical samples, and across a range of diagnoses. 109 It has been proposed that several psychological processes may be involved in the development of psychotic symptoms among trauma survivors, including patterns of emotion regulation developed to cope with trauma, unique qualities associated with memories of traumatic events (including encoding, retrieval, and processing), and changes to personal semantic memory.…”
Section: Theories Of Prereflective Change In Psychosismentioning
confidence: 99%
“…Traumatic events are the prototype of eminently interpersonal, environmental factors that could significantly destabilize and alter subjective experience at various levels. 106 A history of neglect significantly increases the likelihood of developing schizophrenia (and other forms of clinical symptomology) 107,108 ; traumatic and other adverse events are also associated with the development of hallucinations in both clinical and nonclinical samples, and across a range of diagnoses. 109 It has been proposed that several psychological processes may be involved in the development of psychotic symptoms among trauma survivors, including patterns of emotion regulation developed to cope with trauma, unique qualities associated with memories of traumatic events (including encoding, retrieval, and processing), and changes to personal semantic memory.…”
Section: Theories Of Prereflective Change In Psychosismentioning
confidence: 99%
“…Corstens & Longden (2013) found that 94% of voice-hearers (the majority of whom had been diagnosed with schizophrenia) had voices whose content could be related to earlier emotionally overwhelming events. A number of other studies have also reported associations between the nature of stressors/traumas preceding AVH and the content of the ensuing AVH (Hardy et al, 2005; Thompson & Waltz, 2010; Raune et al, 2006; Rosen et al, 2017).…”
Section: Introductionmentioning
confidence: 96%
“…These circumstances include poverty and disadvantage. However, Rosen et al (2017) highlight a lack of previous research on psychosis and traumatic experiences in African Americans.…”
Section: Introductionmentioning
confidence: 96%
“…In this article, I look at three recent articles about the experiences of people of Black African and African Caribbean heritage, in relation to psychosis services in the UK and the USA. Rosen et al (2017) have extended research on traumatic life events and psychosis to Black Americans. Wagstaff et al (2018) report on their in-depth interviews with seven Black men in the UK about their experience of mental health services, shedding important light on why professionals often see them as disengaging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation